2005
DOI: 10.1115/1.1866168
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Removal Rate Model for Oxide CMP

Abstract: This study seeks to explain removal rate trends and scatter in thermal silicon dioxide and PECVD tetraethoxysilane-sourced silicon dioxide (PE-TEOS) CMP using an augmented version of the Langmuir-Hinshelwood mechanism. The proposed model combines the chemical and mechanical facets of interlevel dielectric (ILD) CMP and hypothesizes that the chemical reaction temperature is determined by transient flash heating. The agreement between the model and data suggests that the main source of apparent scatter in remova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 12 publications
1
39
0
Order By: Relevance
“…Based on the initial experimental conditions from which the model was developed, this study attempted to verify the application and use of the model using alternate consumables and an alternate tool set. 5 Removal rate results from this study showed similar systematic scattering effects to in the results shown from the original study. By applying the flash heating model to the results acquired from this study, it was evident that the predictive capability of the flash heating model was more accurate than previously established models.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Based on the initial experimental conditions from which the model was developed, this study attempted to verify the application and use of the model using alternate consumables and an alternate tool set. 5 Removal rate results from this study showed similar systematic scattering effects to in the results shown from the original study. By applying the flash heating model to the results acquired from this study, it was evident that the predictive capability of the flash heating model was more accurate than previously established models.…”
Section: Discussionsupporting
confidence: 87%
“…5 The study involved a set of ILD polishes conducted on a Speedfam IPEC-472 platform with a Rohm and Haas IC-1400 K-groove pad and Cabot D7300 fumed silica slurry. Removal rate results from the study showed consistent and significant deviations from Prestonian behavior.…”
mentioning
confidence: 99%
“…In aqueous systems with constant mechanical interactions, it is difficult to determine the rate-limiting processes. Many semi-empirical CMP models are based on this mechanism by including a fractional surface coverage term in the chemical and mechanical removal rate expression [30][31][32][33]. However, there is room for improvement in the existing models if the chemistry of the oxidation, complexation, and inhibition mechanisms could be better defined, to include rate constants and activation energies that can be found in the literature.…”
Section: Introductionmentioning
confidence: 98%
“…The decrease, 2000 Å /min, is about 10 times the experimental error. Similar fluctuations can also occur in silicon dioxide polishing data [19]. Figure 6.5 shows a contour plot of the same removal rate data as a function of p and V separately (solid lines) with contours of constant pV superimposed for comparison (dashed lines).…”
Section: A Polishing Examplementioning
confidence: 83%
“…The model contains five parameters, E, A, c p , b, and e, but there is a problem with using E as a fitting parameter. The problem is that a polishing experiment conducted at room temperature in which the chemical rate constant (6.40b) and the reaction temperature T are not directly measured does not provide enough information to reliably estimate E. In fact, for any assumed value of E over a reasonable range (say 0.25-1.1 eV), optimization of the remaining four parameters in the above theory will produce nearly identical root mean square (RMS) fitting errors [19]. The reason for this is that over a narrow range of temperatures, such as in Fig.…”
Section: A Polishing Examplementioning
confidence: 99%